A novel embedding method to increase capacity and robustness of low-bit encoding audio steganography technique using noise gate software logic algorithm - Ahmed, M.A.; Kiah, M.L.M.; Zaidan, B.B.; Zaidan, A.A. (Asian Network for Scientific Information (ANSINET), 2010)
In this study, we developed a novel method that is able to shift the limit for transparent data hiding in audio from the fourth LSB layer to the eighth LSB layer, thus the method has improved the capacity and robustness of data hiding in the audio file using a two steps approach. In the first step, noise gate software logic used to obtain a desired signal for embedding the secret message of the input host audio signal (carrier). In the second step, standard 8th LSB layer embedding has been done for this desired signal. Audio quality evaluation has used to evaluate our purposed method in two ways. First, objective test showed the algorithm succeeds in this task, while increasing SNR values of our algorithm comparing to SNR values obtained by standard LSB embedding in the 8th bits LSB layer and the comparison of the histogram audio excerpts has proved this also. Second, subjective listening test proved that high perceptual transparency is accomplished even if eight LSB of host audio signal are used for data hiding.